Mitochondrial sirtuin 4 shapes the intestinal microbiota of Drosophila by controlling lysozyme expression - Mirjam Knop; Christian Treitz; Stina Bettendorf; Judith Bossen; Jakob von Frieling; Shauni Doms; Abdulgawaad Saboukh; Iris Bruchhaus; Ronald P. Kühnlein; John F. Baines; Andreas Tholey; Thomas Roeder (Animal Microbiome)
Abstract Background Sirtuins are deacetylases that are highly conserved throughout the animal kingdom. They act as metabolic sensors that coordinate cellular responses, allowing an adapted response to various stressors. Epithelial cells, especially those of the intestine, are directly exposed to a wide range of stressors. Together with the microbiota, they form a complex ecosystem with mutual influences. The significance of sirtuins in this complex system is still waiting to be clarified. Results Here, we show that a protein-restricted diet strongly increases the intestinal expression of sirtuin 4 (dSirt4), the only mitochondrial sirtuin in Drosophila. To elucidate the effects of deregulated dSirt4 expression in the intestine, we analyzed dSirt4 knockout flies. These flies showed substantial changes in their intestinal proteome and physiological properties. One of the most striking effects was the strong induction of lysozymes in the intestine, with a corresponding increase in lysozyme activity. This effect was organ-autonomous, as it was also observed in flies with dSirt4 knocked out only in intestinal enterocytes. The significant increase in lysozyme abundance in response to tissue-specific dSirt4 knockdown did not reduce the total number of bacteria in the intestine. However, it did affect the microbiota composition by reducing the number of gram-positive bacteria. This effect on microbiota composition can be attributed to dSirt4-dependent lysozyme expression, which is absent in a lysozyme-deficient background. dSirt4 knockout in the enterocytes shortened the lifespan of the flies, as did ectopic lysozyme overexpression in the enterocytes. Conclusions The only mitochondrial sirtuin in Drosophila, dSirt4, is induced by dietary stress in intestinal epithelial cells, which directly regulates the lysozyme activity of these cells. We could associate this altered lysozyme activity with a shift in the microbiota composition, demonstrating a direct link between stress, nutrition, and the host’s microbiota regulation.